Tometes camunani (Characiformes: Serrasalmidae), a new species of phytophagous fish from the Guiana Shield, rio Trombetas basin, Brazil - ANDRADE, Marcelo Costa (2014)
A new species of Serrasalmidae, Tometes camunani, is described from the upper drainages of the rio Trombetas basin, Pará State, Brazil. The new species is distinguished from its congeners by having neurocranium with a slight concavity at the level of the frontal bone (vs. concavity absent, dorsal profile of neurocranium straight). It can be further distinguished from its congeners by having teeth with central cusp taller and acute (vs. central cusp shorter and with rounded edge in T. trilobatus), a terminal mouth (vs. upturned mouth in T. lebaili), and 12-26 prepelvic spines (vs. 0-9 in T. makue). The new species is strictly rheophilic like other species of Tometes, and occurs exclusively in the rapids of shield rivers, complex and fragile biotopes that are threatened by anthropogenic activities. An identification key to the species of the Myleus group is provided.